When Knowledge Is Demotivating - Hadar, Liat; Sood, Sanjay (Psychological Science, 2014)
People find it appealing to have more options to choose from, but the provision of choice often leads to adverse consequences for decision makers’ motivation, satisfaction, and willingness to act. We propose that the effect of the number of choice options on willingness to purchase is moderated by people’s subjective knowledge (SK). The results of three studies provide converging evidence that, paradoxically, people who feel unknowledgeable (low-SK people) in a certain domain are especially willing to purchase when more choice options are available, which is consistent with the notion of “more is better.” This pattern is reversed for people who feel knowledgeable (high-SK people), which is consistent with prior evidence for choice overload. We also show that this pattern is influenced by the informativeness of the features of the available choice options and that subjective knowledge mediates this effect.